Tayma, Saudi Arabia. An Early Bronze Age Domestic Context in the Center of the Settlement. Season 2022 - Lora, Sebastiano (e-Forschungsberichte des DAI, 2023)
As part of the publication of the results of the long-term project (DFG) of the Orient Department in the Tayma Oasis (Saudi Arabia), the archaeological contexts of the Early Bronze Age (3rd millennium BCE) in the centre of the ancient settlement are reviewed and prepared for publication. The contribution deals with architectural contexts of domestic character. The reconstructed stratigraphic sequence offers important clues to the pottery chronology of Tayma and to the way of life at the time of early oasis cultivation. The work was supported by a research grant from the DAI.